Determining optimal phosphorus rates and deficit irrigation levels for enhanced soybean productivity in Jawi District, Northwest Ethiopia - Adametie, Temesgen F.; Selie, Abeba H.; Mitku, Demeke T.; Megerssa, Mesfin K.; Alamenie, Misganew A. (Frontiers in Agronomy, 2024)
Determining the optimal phosphorus rates and deficit irrigation levels is key to enhancing soybean productivity in the Jawi District, Northwest Ethiopia. Soybean is a vital cash crop in Jawi District, Northwest Ethiopia, and improving its productivity is crucial for food security and community socioeconomic status. The optimal phosphorus and deficit irrigation rates in this region remain unresolved. The aim of this study was to optimize soybean productivity in this region by determining the optimal phosphorus rates and deficit irrigation levels. The experiment was conducted during irrigation seasons 2021/22 and 2022/23 using a split-plot design with an RCBD arrangement. The results showed that combining P rates of 10, 20, 30, and 40 kg ha-1 with 100% ETc. significantly increased soybean grain production. Similarly, soybean grain yield increased at P rates of 0, 10, 20, 30, and 40 kg ha-1 P with 75% ETc. The highest water productivity recorded was 0.29 kg m-3 at 50% ETc. This study suggests that combining P rates of 10, 20, 30, and 40 kg ha-1 P with 100% ETc. and P rates of 0, 10, 20, 30, and 40 kg ha-1 P with 75% ETc. could significantly enhance soybean productivity. Implementing these strategies could lead to more sustainable and efficient agricultural practices in Jawi District, thereby improving crop yields and overall profitability.